2020
DOI: 10.1055/s-0039-1690834
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of the Enantiomers of Thioridazine

Abstract: Thioridazine, a well-known antipsychotic drug, has shown promising effects on several bacterial strains (including Mycobacterium tuberculosis and methicillin-resistant Staphylococcus aureus). Suppressive effects towards selected cancer cell-lines have also been reported. However, due to adverse effects, the compound is no longer in use for the primary indication. More recent research has demonstrated that these side effects are limited to one of the two enantiomers, (+)-thioridazine. The question arises to whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Especially, the MeS functional group needs to be introduced in the initial step. Here, MeS group was successfully introduced into the compound in the last step with MTBT as a “MeS” shuttle in a decent yield (70 %) as shown in Scheme 5a, providing a new synthetic route for 3 z , which may reduce the cost of the medicine [30–31] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Especially, the MeS functional group needs to be introduced in the initial step. Here, MeS group was successfully introduced into the compound in the last step with MTBT as a “MeS” shuttle in a decent yield (70 %) as shown in Scheme 5a, providing a new synthetic route for 3 z , which may reduce the cost of the medicine [30–31] …”
Section: Resultsmentioning
confidence: 99%
“…Here, MeS group was successfully introduced into the compound in the last step with MTBT as a "MeS" shuttle in a decent yield (70 %) as shown in Scheme 5a, providing a new synthetic route for 3 z, which may reduce the cost of the medicine. [30][31] Sulfides and bromide groups have orthogonal chemical reactivities. [32] The former ones were usually functionalized in classic Liebeskind-Srogl reaction, which tolerated most crosscoupling reaction conditions when using aryl bromides as electrophiles.…”
Section: Chemistry-a European Journalmentioning
confidence: 99%
“…This underlines the importance of having good procedures for the synthesis of the optically pure enantiomers, something that has been found to be unsatisfactory for the drug thioridazine. Antonsen S. has used an auxiliary-based strategy for the total synthesis of both enantiomers in high optical purity [ 118 ]. Ongoing studies have shown that the antimicrobial effects of these two enantiomers are similar [ 118 ], but further investigations are needed to determine whether the side effects are caused by one or both enantiomers.…”
Section: Discussionmentioning
confidence: 99%
“…Antonsen S. has used an auxiliary-based strategy for the total synthesis of both enantiomers in high optical purity [ 118 ]. Ongoing studies have shown that the antimicrobial effects of these two enantiomers are similar [ 118 ], but further investigations are needed to determine whether the side effects are caused by one or both enantiomers. In situations where the side effects are caused by only one enantiomer, pure-enantiomeric non-antibiotic drugs will open up the possibility for better treatments of resistant bacterial infections.…”
Section: Discussionmentioning
confidence: 99%